Treatment expectancy, working alliance, and outcome of Trauma-Focused Cognitive Behavioral Therapy with children and adolescents - Veronica Kirsch; Ferdinand Keller; Dunja Tutus; Lutz Goldbeck (BMC, 2018)
Abstract Background It has been shown that positive treatment expectancy (TE) and good working alliance increase psychotherapeutic success in adult patients, either directly or mediated by other common treatment factors like collaboration. However, the effects of TE in psychotherapy with children, adolescents and their caregivers are mostly unknown. Due to characteristics of the disorder such as avoidant behavior, common factors may be especially important in evidence-based treatment of posttraumatic stress symptoms (PTSS), e.g. for the initiation of exposure based techniques. Methods TE, collaboration, working alliance and PTSS were assessed in 65 children and adolescents (age M = 12.5; SD = 2.9) and their caregivers. Patients' and caregivers' TE were assessed before initiation of Trauma-Focused Cognitive Behavioral Therapy (TF-CBT). Patients' and caregivers' working alliance, as well as patients' collaboration were assessed at mid-treatment, patients' PTSS at pre- and post-treatment. Path analysis tested both direct and indirect effects (by collaboration and working alliance) of pre-treatment TE on post-treatment PTSS, and on PTSS difference scores. Results Patients' or caregivers' TE did not directly predict PTSS after TF-CBT. Post-treatment PTSS was not predicted by patients' or caregivers' TE via patients' collaboration or patients' or caregivers' working alliance. Caregivers' working alliance with therapists significantly contributed to the reduction of PTSS in children and adolescents (post-treatment PTSS: β = − 0.553; p < 0.001; PTSS difference score: β = 0.335; p = 0.031). Conclusions TE seems less important than caregivers' working alliance in TF-CBT for decreasing PTSS. Future studies should assess TE and working alliance repeatedly during treatment and from different perspectives to understand their effects on outcome. The inclusion of a supportive caregiver and the formation of a good relationship between therapists and caregivers can be regarded as essential for treatment success in children and adolescents with PTSS.